2016
DOI: 10.1016/j.jcp.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A fast band–Krylov eigensolver for macromolecular functional motion simulation on multicore architectures and graphics processors

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The details of our NMA framework in internal coordinates were described previously and are similar to those implemented in ref . Briefly, the internal mobile coordinates are defined by the canonical backbone dihedral angles, while the remaining dihedral angles and all covalent bond lengths and angles are fixed.…”
Section: Methodsmentioning
confidence: 99%
“…The details of our NMA framework in internal coordinates were described previously and are similar to those implemented in ref . Briefly, the internal mobile coordinates are defined by the canonical backbone dihedral angles, while the remaining dihedral angles and all covalent bond lengths and angles are fixed.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have reported about GPU implementation of Krylov eigensolvers. For instance, Aliaga et al [8] accelerates Krylov methods by off-loading the matrix-vector products to the GPU, after carrying out a band reduction of the matrix (and losing the sparse character). This work is restricted to computing exterior eigenvalues of symmetric matrices, while our main concern is interior eigenvalues of non-symmetric block-tridiagonal matrices.…”
Section: Introductionmentioning
confidence: 99%